Supramolecular Nanofibers Formed by Enzyme‐Instructed Self‐Assembly for SKBR‐3 Cell Selective Inhibition. Issue 14 (23rd May 2022) - Wang, Shijiang; Ma, Yan; Ma, Changsheng; Liu, Kai; Huo, Zhijun; Shang, Yuna
Abstract: Cell‐targeted peptides are recommended for precision cancer treatment due to their comparable targeting properties, small molecular size, and good biocompatibility. However, unpredictable bioactivity, low penetration rate and poor stability greatly limit its efficacy. Supramolecular self‐assembly based on synthetic peptide has great potential to solve related problems and achieve better therapeutic effects. Herein, we report and compare the effects of two different assembly pathway, heating‐cooling, and enzyme instruction, on the penetrability of SKBR‐3 cell targeted peptides. It was found that enzyme‐instructed self‐assembly (EISA) resulted in hydrogels composed of uniform supramolecular nanofibers, whereas heating‐cooling resulted in solutions and precipitations composed of slightly different nanoparticles. The nanofibers formed by EISA showed enhanced cellular uptake (2.54 μM), which was significantly higher than the 1.06 μM of the nanoparticles formed by temperature regulation. Thus, EISA is a promising strategy to improve the cell penetration rate of targeted peptides and could provide a better solution for precision cancer treatment. Abstract : We compare the effects of two different assembly pathway, heating‐cooling, and enzyme instruction, on the penetrability of SKBR‐3 cell targeted peptides. It is found that enzyme‐instructed self‐assembly (EISA) results in hydrogel composed of uniform supramolecular nanofibers, which exhibit enhanced cellular uptake and selective cytotoxicity. EISA is a promising strategy to improve the cell penetration rate of targeted peptides and could provide a better solution for precision cancer treatment.